Kádár János nyugdíjba megy - Mery, Zsuzsa (Hungary, 2001)
Secretary general of the Communist Party Janos Kadar requested his retirement in 1972 which however never materialized. What was behind this request? Who was it addressed to? To Leonyid Brezhnev? Who wrote it? An old, tired man or a cunning politician?
Duration: 00:45:00
Keywords: Documentary films